Strategi Marketing Public Relations dalam Mempertahankan Citra Perusahaan Konstruksi Artekindo Group - Nurjayanti, Nurjayanti; Sanmas, Masni; Abidin, Andi Saenal; Hasrul, Hasrul (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2024)
Data from the Central Statistics Agency (Badan Pusat Statistik) records that until 2020, there were 130,743 companies providing construction services in Indonesia. This large number results in tight competition in attracting clients. Competition became more complex during the Covid-19 pandemic which resulted in companies providing construction services experiencing difficulties, one of which was the Artekindo Group which was founded in the city of Jayapura, Papua province. This research aims to find out and describe strategiesMarketing Public Relations which is used in forming or building the Artekindo Group company image so that it can survive amidst the intense competition that is currently occurring. The object of this research is strategyMarketing Public Relations in forming or building a company image. The approach used is descriptive qualitative with data collection methods in the form of interviews, observation and documentation. The data analysis technique consists of three flows, namely data reduction, data presentation, and drawing conclusions. This research shows the results that strategyMarketing Public Relations What Artekindo Group applies in forming its image is:pull strategy, push strategy, andpower strategy. The three strategies implemented have proven successful in making Artekindo Group survive and able to gain clients even in difficult conditions.